Quality assessment of water and wastewater - Tomar, Mamta (Lewis, 1999)
Water is the most basic need of mankind. Drinking water is considered the most essential use of water in life. Therefore it must be free of pathogens, toxins and carcinogens.Absolutley pure water does not exist in nature. Surface water absorbs particles, carbon dioxide and other gases and mixes with silt and inorganic matters from the environment. When treated and untreated domestic and industrial waste is discharged into natural bodies of water the situation becomes even more complex. Thus human waste, drinking water and communicable diseases are directly related. Water contamination is measured by the level of pollutants present in a sample. Regular analytical estimation of wastewater is the answer. This manual emphasizes the importance of water purity for drinking and domestic purposes, different types of water and their utilization in various activities, the water quality requirements and criteria of International and Governmental Agencies, and simple estimation procedures and the significance of each analytical test. Quality Assessment of Water and Wastewater describes methods for ascertaining the quality and contamination levels of waters from a range of sources like ground, surface, potable water supplies, marine, beaches, swimming pools and other recreational facilities, and domestic and industrial wastewater. It includes important derivatives used in the preparation of standard solutions, data analysis, interpretation and units of expressions of the results. It also discusses all major pollutants - their origins and impact on the environment and health - with the basic chemistry of their analysis and complete methodology explained systematically.